Standard methods for Apis mellifera beeswax research. Issue 2 (15th March 2019) - Svečnjak, Lidija; Chesson, Lesley Ann; Gallina, Albino; Maia, Miguel; Martinello, Marianna; Mutinelli, Franco; Muz, Mustafa Necati; Nunes, Fernando M.; Saucy, Francis; Tipple, Brett James; Wallner, Klaus; Waś, Ewa; et al.
Abstract : Due to its multifunctional and complex role in the honey bee colony functioning and health (construction material allowing food storage, brood rearing, thermoregulation, mediation in chemical and mechanical communication, substrate for pathogens, toxins and waste), Apis mellifera beeswax has been widely studied over the last five decades. This is supported by a comprehensive set of scientific reports covering different aspects of beeswax research. In this article, we present an overview of the methods for studying chemical, biological, constructional, and quality aspects of beeswax. We provide a detailed description of the methods for investigating wax scales, comb construction and growth pattern, cell properties, chemical composition of beeswax using different analytical tools, as well as the analytical procedures for provenancing beeswax and beeswax-derived compounds based on the hydrogen isotope ratio (IRMS). Along with classical physico-chemical and sensory analysis, we describe more precise and accurate methods for detection of adulterants in beeswax (GC-MS and FTIR-ATR). Moreover, we present methods for studying the influence of beeswax (comb foundation) adulteration on comb construction. Analytical protocols for determining the pesticide residues using different chromatographic and spectroscopic techniques are also described. As beeswax is an agent of high risk for the transmission of bee diseases, we present methods for detection of pathogens in beeswax. To ensure the reproducibility of experiments and results, we present best practice approaches and detailed protocols for all methods described, as well as their advantages and disadvantages. Métodos estándar para la investigación de la cera de abejas Apis mellifera Debido a su papel multifuncional y complejo en el funcionamiento y la salud de la colonia de abejas melíferas (material de construcción que permite el almacenamiento de alimentos, la cría, la termorregulación, la mediación en la comunicación química y mecánica, el sustrato para patógenos, toxinas y desechos), la cera de las abejas Apis mellifera ha sido ampliamente estudiada en las últimas cinco décadas. Esto se apoya en un amplio conjunto de informes científicos que abarcan diferentes aspectos de la investigación sobre la cera de abejas. En este artículo presentamos una visión general de los métodos que permiten el estudio químico, biológico, estructural y cualitativo de dicha cera. Proporcionamos una descripción detallada de los métodos usados para la investigación de las escamas de cera, la construcción del panal y su patrón de crecimiento, las propiedades de las celdas, y la composición química de la cera utilizando diferentes herramientas analíticas; así como los procedimientos analíticos basados en el ratio de isótopos de hidrógeno (IRMS) que permiten determinar el origen de la cera y los compuestos derivados de ella. Junto con el análisis físico-químico y sensorial clásico, describimos métodos más precisos y exactos para la detección de adulterantes en cera de abejas (GC-MS y FTIR-ATR). Además, presentamos métodos para estudiar la influencia de la adulteración de la cera de abejas (base del panal) en la construcción del panal. También se describen protocolos analíticos para determinar los residuos de pesticidas utilizando diferentes técnicas cromatográficas y espectroscópicas. Dado que la cera de abejas es un agente de alto riesgo en la transmisión de enfermedades de abejas, presentamos métodos para la detección de patógenos en dicha cera. Para garantizar la reproducibilidad de los experimentos y los resultados, presentamos modelos de buenas prácticas y protocolos detallados para todos los métodos descritos, así como sus ventajas y desventajas. 西方蜜蜂蜂蜡研究标准方法 蜂蜡在蜂群功能和健康中具有多种功能和复杂作用（食物储存、哺育幼虫、温度调节的筑巢材料, 化学和机械通讯的中介, 以及病原体、毒素和废物的基质）, 因此西方蜜蜂蜂蜡在过去五十年中被广泛研究。这得到了一套全面科学报告的支持, 涵盖了蜂蜡研究的不同领域。本文概述了蜂蜡的化学、生物、结构和质量的研究方法。本文详细介绍了利用不同分析工具研究蜡鳞、筑巢, 蜂蜡的生长方式、细胞特性和化学成分的方法, 以及基于氢同位素比值 (IRMS) 的蜂蜡和蜂蜡衍生化合物的来源分析方法。除了经典的物理化学和感官分析, 我们还描述了更精准的检测蜂蜡掺假的方法（GC-MS和FTIR-ATR）。此外, 我们还研究了蜂蜡（巢础）造假对蜂巢结构的影响。还介绍了使用不同色谱和光谱技术测定农药残留的分析流程。由于蜂蜡是传播蜜蜂疾病的高危因素, 我们提出了检测蜂蜡中病原体的方法。为了确保实验和结果的可重复性, 我们为所描述的所有方法提供了最佳实践方法和详细流程, 以及它们的优缺点。